BREAST CANCER SCREENING IN WOMEN AGED 45-65 IN SAMARKAND REGION, UZBEKISTAN: A CROSS-SECTIONAL ANALYSIS OF DATA FROM 2023 - L.Sh., Yorov (PT. Antis International Publisher, 2024)
Objective: Breast cancer remains a leading cause of cancer-related mortality among women globally. Early detection through screening significantly reduces both morbidity and mortality. This study aims to evaluate the outcomes of breast cancer screening programs conducted in the Samarkand region of Uzbekistan in 2023, with a focus on participation rates, detection rates, and stage distribution across 17 districts and cities. Methods: Data were collected for women aged 45–65, including annual screening targets, the number of screenings performed, diagnosed cases, and cancer stage distribution (early stages 1–2 vs. late stages 3–4). Statistical analysis was used to determine screening completion and detection rates, as well as to assess regional disparities in program outcomes. Results: The screening program yielded promising results in terms of participation and early-stage cancer detection. A higher proportion of breast cancer cases were identified at early stages (1–2), indicating effective diagnosis in several areas. However, notable regional disparities were observed in both screening completion and detection rates, reflecting unequal access to services across districts. Novelty: This study provides a comprehensive regional analysis of breast cancer screening outcomes in Uzbekistan. It highlights the urgent need to address disparities in healthcare access to ensure equitable early diagnosis and treatment. The findings emphasize the importance of targeted public health interventions aimed at improving screening program effectiveness and reducing the burden of late-stage breast cancer.